Evaluasi Kinerja Marketing Menggunakan Metode Simple Additive Weighting (SAW) Berbasis WEB pada PT. XYZ Group - Lubis, Hendarman; Fitriyani, Aida; Hendharsetiawan, Andy Achmad (Journal of Information System, Informatics and Computing, 2024)
XYZ Group is an independent property consulting company that provides services ranging from consulting services to running an effective, efficient and professional sales system with a mission in the field of housing sales. The core problem that exists is that the employee assessment process is still conventional so it takes a long time and there is no system and application that supports the employee assessment process. The methodology used in this research is: Observation Methodology, Interview Methodology, Literature Methodology. The software development used is the RAD method, in this method there are three stages, namely: Requirements Planning, RAD design workshop, Implementation. In designing the decision support system at PT.XYZ Group using the Rapid Application Development (RAD) method. After the system has been analyzed and designed in detail, the next stage that will be carried out is the system implementation stage in the form of implementing a decision support system at PT.XYZ Group which is ready to be used. The aim of the system design concept that has been prepared is so that if an error occurs in the system it can be corrected again. This Decision Support System can make it easier for the company to determine the best marketing person who will fill the position being promoted. The Decision Support System is able to provide alternatives in determining the best marketing using the Simple Additive Weighting (SAW) method. The output from this Decision Support System can sort employee rankings from highest to lowest, as well as print reports on the best marketing results.